Pharmacogenetics and Pharmacokinetic of Azithromycin Eyedrops in Meibomian Gland Dysfunction Treatment - Syena Damara Riza Gustam (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2021)
Meibomian gland dysfunction (MGD) is the leading cause of ocular surface disease throughout the world, which has a prevalence that varied widely from 3.5 to 70% according to age, sex, and ethnicity. Azithromycin (AZM) is the first azalidic antibiotic, a class of macrolide antibiotics, which has derived from erythromycin. It is widely used in clinical practice, not only for respiratory diseases and sexually transmitted infections but also for ocular diseases. azithromycin suppressed zymosan-induced mRNA expression and protein production of proinflammatory cytokines (tumor necrosis factor α and IL-1β), chemokines (IL-6 and RANTES), and MMPs (MMP-1, MMP-3, and MMP-9) by human corneal epithelial cells and suggested the potential for using azithromycin to treat ocular surface It controls the initiation and resolution of inflammatory responses through the regulation of chemotaxis, activation, and survival of lymphocytes. The anti-inflammatory role of TGF-β1 has been recognized in different cell types by inhibiting proinflammatory cytokines including tumor necrosis factor α, IL-1, and interferon γ.The combination of a topical AZM solution 1.0% with corticosteroid (DEX 0.1%) was found superior in the comprehensive treatment of MGD after 2 weeks. AZM is a one of the safest antibiotics, well tolerated, and has special pharmacokinetic properties. Moreover, it has a broad antimicrobial spectrum. AZM is efficacious for the treatment of a lot of ocular diseases and may be included as monotherapy or in combination therapy in new treatment protocols for more ocular infections.